Humanitarian Journalists : Covering Crises from a Boundary Zone. - Scott, Martin. (Routledge Focus on Journalism Studies, 2023)
This book documents the unique reporting practices of humanitarian journalists - an influential group of journalists defying conventional approaches to covering humanitarian crises. It will interest students and scholars of journalism and communication studies, sociology, and humanitarian studies.